2016
DOI: 10.5539/mas.v10n10p193
|View full text |Cite
|
Sign up to set email alerts
|

Barley Grain Yield and Protein Content Response to Deficit Irrigation and Sowing Dates in Semi-Arid Region

Abstract: The present study was conducted to investigate the relational effects of various sowing dates and deficit irrigation on grain yield, protein and yield components of barley, in a semi-arid region (southern part of Iran) during growing seasons 2011-2012 and 2012-2013. A Split plot layout within a randomized complete block design with three replications was used. Main plots were selected as Irrigation treatments with varying water irrigation levels consisting of: (1) full irrigation, FI, (2) 0.75 FI, (3) 0.5 FI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…As for the effect of planting dates, the results of Table (5) showed that the date (30/11) was superior in protein content with an average of (14.060)%, followed by the two dates (20/11 and 1/11) and without a significant difference between them, as they recorded averages of (12,300 and 12,300) 12.200)%, while the date (10/11) the lowest average score for this attribute, totaling (11.737)%, and the reason for the superiority of the date (30/11) in the percentage of protein may be due to the delay in the date of planting with the high temperature and low relative humidity. Which leads to stress of the fruit parts, so their contribution to food manufacturing decreases, so the plant depends on the materials transferred to it from the vegetable part, which are mostly protein materials, and this leads to an increase in protein in the grains, this result agreed with [20] who found an increase in protein with the late planting date.…”
Section: Weight 1000 Grains (G)supporting
confidence: 77%
See 1 more Smart Citation
“…As for the effect of planting dates, the results of Table (5) showed that the date (30/11) was superior in protein content with an average of (14.060)%, followed by the two dates (20/11 and 1/11) and without a significant difference between them, as they recorded averages of (12,300 and 12,300) 12.200)%, while the date (10/11) the lowest average score for this attribute, totaling (11.737)%, and the reason for the superiority of the date (30/11) in the percentage of protein may be due to the delay in the date of planting with the high temperature and low relative humidity. Which leads to stress of the fruit parts, so their contribution to food manufacturing decreases, so the plant depends on the materials transferred to it from the vegetable part, which are mostly protein materials, and this leads to an increase in protein in the grains, this result agreed with [20] who found an increase in protein with the late planting date.…”
Section: Weight 1000 Grains (G)supporting
confidence: 77%
“…
The experiment was carried out in one of the farms affiliated to the Department of Agricultural Extension / Ministry of Agriculture, in Muthanna Governorate / Warka District (25 km away from the governorate center), during the season (2021)(2022) in order to study the effect of four planting dates (1,10,20, 30\November) on yield components and qualitative traits of a number of genotypes (G1, G2, G3, G4, G5, G6, G7, G8, G9) and Aba265 (G10) of barley crop. The experiment was applied using the design of completely randomized sectors according to split method With three replications, as the dates filled the main panels and the structures in the secondary panels, the results of the experiment showed: Most of the genotypes outperformed in both yield components and qualitative traits, as genotype G7 outperformed in the trait of number of spikes with an average of (610.3) spike m -2 , and genotype G9 outperformed in the number of grains per spike with an average of (43.92) grains of spike m -1 , Aba265 (G10) was superior in the trait of weight of one thousand grains with an average of (47.06) g, and for the character of the protein content in the grains, the genotypes G6, G1, G8, and G10 excelled without a significant difference between them with averages of (13.342, 13.225, 13.037 and 12.950)% Sequentially, the G1 genotype was superior to the specific weight and without a significant difference from the genotypes G2, G8, G6 and G3, where their averages reached (63.52, 63.47, 62.82, 62.58 and 62.40) kg hectoliter -1 respectively.
…”
mentioning
confidence: 99%
“…It was noted from the result of table (6 ) that the planting date of November 15 was superior , giving it the highest average protein percentage of 8.38 % , compared to the planting date of October 1 , which gave the lowest average of 6.15 % the reason may be due to the suitability of environmental factors ,such as temperature ,humidity, and lighting ,which in turn affected the nutritional representations within the plant and thus increased the percentage of protein due to the efficiency of the nitrogen fixation process, this result was agreed upon [17] by those who found an increase in protein by delaying the planting date. As for the varieties, the Samir variety achieved the highest average for this trait, amounting to 7.339%, and did not differ significantly from the variety Rehan, Buraq, and Shuaa, which gave values of 7.384, 7.224, and 7.196%, respectively, while the Arevat variety gave the lowest average, amounting to 6.562%, and did not differ significantly from the two varieties Amal and Ebaa 99.…”
Section: The Percentage Of Protein %mentioning
confidence: 58%
“…Thus optimized regulated deficit irrigation was recommended in areas with a low amount of irrigation water. A former study conducted on barley reported highest water use efficiency of the crops under 50% full irrigation (Tabarzad et al, 2016). Likewise, several previous studies have reported the positive effect of limited irrigation on the yield and W UE of crops (Pardo et al, 2020;Kang et al, 2000;Djaman et al, 2020a).…”
Section: Effect Of Irrigation and Mixed Cropping On Water Productivitymentioning
confidence: 79%